A modified Shiller's cyclically adjusted price-to-earnings (CAPE) ratio for stock market index valuation in a zero-interest rate environment. Issue 1 (2nd January 2022) - Catanho, Roberto; Saville, Adrian
ABSTRACT: The cyclically adjusted price-earnings ratio (CAPE) is a tool that has become widely used to predict market returns. However, recently, deterioration in its forecast strength has surfaced. At the same time, global long-term interest rates have declined and are expected to remain at record lows, which the CAPE fails to consider. Omitting to fully examine the impact of the cost on capital on the effectiveness of CAPE as a valuation tool represents a gap in knowledge. This study uses a modified CAPE to account for interest rates, known as the excess CAPE yield (ECY), to offer an alternative – and potentially improved – model for predicting global stock market returns. We find that CAPEs peak when real interest rates are between 3% and 5%, while the ECY fails to improve on the predictive abilities of the CAPE.